“How high net worth individuals account for a perceived shift in their personal consumption from luxury goods to luxury services” - Marmiss, Vitalijs (2015)
The research project provides the discussion of consumer preferences shift phenomenon from luxury goods to luxury services and how high net worth individuals account for a mentioned perceived shift in their personal consumption. The dissertation begins with the description of chosen topic background and recitation of relevant objectives addressed to an explanation of consumer preferences shift phenomenon. Then, the literature review provides comprehensive definition of luxury goods and services and emphasizes the key differentiation aspects among them from consumer behavior theory perspective. Which revealed that both types of luxury commodities frequently overlap each other by forming mixed types commodities, which arranged in the service-goods continuum and satisfy psychological and functional inner needs of customers. Furthermore, the investigation of mentioned consumer behavior in the context of luxury possession has explored the existence of four customers’ profiles, who have different motivations for purchasing luxury commodities. Therefore, academics states that the process of individual’s consumption preferences shift is the result of changed values of consumers and occurred motivation of acquiring other type of commodity that will be able to satisfy transformed value end-state of mind. In addition, the overview of worldwide luxury market has confirmed the existence of consumption preferences shift from luxury goods to luxury services as common present tendency among high net worth individuals that improved the credibility of the research project. The further part of assignment discusses the appropriateness of utilization chosen interpretivism research philosophy, deductive approach, unstructured data collection and narrative analysis methods for successful accomplishment of the main research investigation question. Finally, the primary research of the assignment sufficiently supplemented the theoretical findings of the secondary research. The further analysis of wealthy individuals’ interviews lead to the conclusion that single customer might represent all mentioned types of consumer profiles depending on emerged needs. Moreover, the individual’s shift in personal consumption from luxury goods to luxury services might perform cyclical type process that occurs in the case of considerable development of wealth level and further attainment of oversaturation point considering luxury goods acquiring. Rather than straight and irretrievable motion from materialist valued state of being to hedonic valued state, which described by academics.